1992
DOI: 10.1203/00006450-199204000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Epidermal Growth Factor, Transforming Growth Factor-α, Epidermal Growth Factor Receptor, and Thyroid Hormone Receptor RNA Levels in Rat Kidney and Changes in Those Levels Induced by Early Thyroxine Treatment

Abstract: ABSTRAm. Ontogenic changes in the mRNA levels of epidermal growth factor (EGF), transforming growth factor-a, EGF receptor, and thyroid hormone receptor (rerbA) were examined in developing rat kidneys. The mRNA levels of both EGF and thyroid hormone receptor rose dramatically during the postnatal period with the rise in thyroid hormone receptor message preceding the rise in EGF message. In addition, we examined renal mRNA levels in 1-wk-old rats treated with thyroxine (T4) from birth through d 6. Neonatal T4 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
(17 reference statements)
0
9
1
Order By: Relevance
“…PPAR activity may be released from suppression by TR due to decreased number of TR during fasting, resulting in the increased transcriptional levels of enzymes regulating fatty acid ␤-oxidation such as aox gene. Furthermore, TR expression is regulated by hormones (54) and strictly controlled during ontogeny and development (55)(56)(57)(58). TRs exert their effects on lipid metabolism through convergence of PPAR signaling pathways.…”
Section: Table I Protein Expression Of Tra1 and Its Dbd Mutant In Cosmentioning
confidence: 99%
“…PPAR activity may be released from suppression by TR due to decreased number of TR during fasting, resulting in the increased transcriptional levels of enzymes regulating fatty acid ␤-oxidation such as aox gene. Furthermore, TR expression is regulated by hormones (54) and strictly controlled during ontogeny and development (55)(56)(57)(58). TRs exert their effects on lipid metabolism through convergence of PPAR signaling pathways.…”
Section: Table I Protein Expression Of Tra1 and Its Dbd Mutant In Cosmentioning
confidence: 99%
“…The strong hybridization signal observed in day-20 and neonatal rat kidneys does not completely agree with the low amount of TGFα mRNA found in neonatal rat kidney extracts by other authors [15]: they defined their observation as unexpected and suggested that the reason for the low TGFα mRNA level they found might be ascribed to the mRNA instability.…”
Section: Discussionmentioning
confidence: 43%
“…More recent studies demonstrated that organ cultures of gestational day-13 rat metanephros produce TGFα in vitro, thus suggesting the organogenetic role of the metanephric-derived TGFα [7]. Further experiments carried out in vivo by North et al [15]reported that only small amounts of TGFα mRNA could be extracted from neonatal rat kidneys. In conclusion the presence of this growth factor, necessary for metanephric development, and particularly its related mRNA is still not well documented throughout the sequential stages of renal organogenesis and, although fragmentary results on this matter have been published for rodent embryos, no detailed data are available for the in situ localization of TGFα transcripts in human renal primordia.…”
Section: Discussionmentioning
confidence: 99%
“…T 4 has been shown to augment the levels of EGF mRNA as well as EGF immunoreactivity in neonatal rodent kidneys [7, 17]. Thyroid hormone was also found to upregulate gene expression, synthesis, and release of pro-EGF in adult rat kidneys [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [3, 4, 5, 6] showed evidence of renal origin of urinary EGF in human neonates, developmental patterns of urinary EGF in premature infants, and decreased urinary EGF excretions in neonates with intrauterine growth retardation. In animal experiments, thyroid hormone can enhance renal EGF synthesis and thus increase urinary EGF excretion [7, 8, 9]. The urinary EGF level is high in neonates with hyperthyroidism, whereas it is low in those with hypothyroidism [10].…”
Section: Introductionmentioning
confidence: 99%